Early life factors in relation to cardiovascular risk and cardiovascular disease in old age in Bergen: a Norwegian retrospective cohort study based on the Hordaland Health Study (HUSK). (9th June 2014) - Skogen, Jens Christoffer; Stewart, Robert; Knapstad, Marit; Øverland, Simon; Mykletun, Arnstein
Summary: Objectives: The fetal origins of adult disease hypothesis describes associations found for fetal or early-life exposures with cardiovascular risk and disease in adulthood. The extension or not of these associations into old age has received less attention. We investigated if maternal health and family circumstances were associated with cardiovascular risk factors and cardiovascular disease (CVD) in late life and discuss results in light of possible selection effects and measurement error. Design: A retrospective cohort study based on community survey. We examined 224 possible associations between anthropometric measures, maternal health information and family socioeconomic status at birth versus CVD and CVD-related risk factors 72–74 years later. Participants: Of 3341 participants in a community survey of people aged 72–74 years, we were able to trace birth records from a historical archive in a broadly representative subsample of 480. Setting: Bergen, Norway Main outcome measures: Established cardiovascular risk factors and indicators of CVD. Results: Only 11 (4.9%) of these associations were found to be statistically significant, and no strong or consistent patterns in the associations between exposures and outcomes were found. Conclusions: There was little evidence in this relatively elderly sample for an association between early life factors and CVD outcomes of clinical or public health relevance. Further research is required to confirm the extent to which a diminution of early life influences into old age, if genuine, can be accounted for by selective mortality, systematic bias or by dilution of effects due to competing risk factors.